Spatial Regulation of Protected Rice Fields through A Notary Law Approach on Freehold Title Splitzing - I Made Sudira (Jurnal Hukum Prasada, 2022)
Protected Rice Field is a legal norm regulated in the Decree of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number: 1589/SK-HK.02.01/XII/2021 concerning Stipulation of Protected Rice Fields Map in Regencies/Cities in West Sumatra Province, Banten Province, West Java Province, Central Java Province, Yogyakarta Special Region Province, East Java Province, Bali Province, and West Nusa Tenggara Province. The purpose of the establishment of the regulation is to control the conversion of rice fields into other functions such as housing, shops, offices and other investment functions. A Notary as an official authorized to make an authentic deed, based on the duties and authorities of a Notary regulated in the Notary Position Act, can also execute the process of splitzing a land certificate by first obtaining a position as a Land Deed Official (referred to as PPAT). Problems regarding protected rice fields in relation to the authority of the Notary in executing the splitzing of the certificates of rice fields are there are obstacles that may emerge in the implementation process due to the issuance of regulations regarding the protected rice fields. This study aims to analyse the public’s perception towards the designation of protected rice fields with the provisions of the freehold titles splitzing. The research method used in thi research is normative juridical research. Based on the analysis, the results of this study indicated that in the case splitzing the deeds of rice field land, the notary is still guided by the terms and conditions stipulated by the National Land Agency.